TEKS ANEKDOT DALAM CERTA LISAN DAYAK NGAJU “PALUI” SEBAGAI PEMBELAJARAN BAHASA INDONESIA DI SMA - Yulina Mingvianita; Benny Irawan; Syarah Veniaty; Jumadi Jumadi (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Palui’s story presents an interesting plot through humorous characters and dialogues involving Palui, his mother, and his father. These elements convey implied meanings, jokes, satire, and moral messages. This research focuses on (1) the structure and linguistic features of Palui’s anecdotal texts, (2) their socio-cultural values, and (3) their relevance and integration into Indonesian language learning for Grade X high school students. This study employed a descriptive qualitative method to analyze the anecdotal structure, linguistic features, socio-cultural values, and relevance to learning. The results identified six complete Palui anecdotal stories, distinguished by humorous and satirical elements within the crisis and reaction components. The stories contain socio-cultural values related to children’s obedience, responsibility, ethics, livelihoods, work, local food, traditional tools, and cultural traditions. As Ngaju Dayak oral literature, Palui’s stories are relevant to Grade X Indonesian language learning because their plots contain recognizable anecdotal structures and linguistic features. They can serve as learning references and enrich teaching materials through local-story-based differentiation. Thus, students can understand anecdotes not only as humorous and critical representations of life but also as expressions of local cultural heritage, moral values, and traditional knowledge.